Non - Fluoroscopic Transesophageal Echocardiography Guided Transcatheter Closure of Atrial Septal Defects: Single Centre Experience in The North of Sumatra Island, Indonesia - Ali Nafiah Nasution; Bertha Gabriela Napitupulu; Tengku Winda Ardini; Joy Wulansari Purba; Cut Aryfa Andra; Anggia Chairuddin Lubis; Abdullah Afif Siregar (Jurnal Kardiologi Indonesia, 2026)
Background: Non-fluoroscopic, transesophageal-guided percutaneous closure of Atrial Septal Defect (ASD) can be a first-line strategy to reduce radiation exposure and its cumulative effects. We report our experience as the first center located far from the capital city of Indonesia that routinely performs transcatheter closure of ASD under the guidance of Transesophageal Echocardiography (TEE) without fluoroscopy. Methods: We collected data of patients whose ASD was successfully closed percutaneously from May 2020 to August 2024. For a total of 116 patients of secundum ASD that are suitable for device closure, we routinely intend to do non-fluoroscopy transcatheter ASD closure guided by TEE. Results: The zero-fluoroscopy technique was successfully performed in 111 patients. The ASD diameter is 10-40 mm, and the mean size of the occluding device is 9-42 mm. The mean procedural times are 55.81 ± 22.7 minutes. The success rate is 95% with only one case of pericardial effusion. Five cases were excluded as they were finally assisted by fluoroscopy due to the limitation of the echocardiographic view. Conclusion: A thorough transcatheter ASD closure technique guided by TEE can routinely be performed without fluoroscopy.